Preaching politics: Islam and Christianity on the Kenya coast. Issue 2 (3rd April 2017) - Deacon, Gregory; Gona, George; Mwakimako, Hassan; Willis, Justin
ABSTRACT: Focusing on the Kenya coast, this article analyses the developing contrast between the place of Islam and Christianity in public politics. It argues that Islam's association with criticism of the political order contrasts with Christianity, but that this is not the result of inherent difference between the religions. Both have previously provided a language, and space, for political commentary and activism in Kenya. The contrast is rather the contingent result of particular circumstances in Kenya. Christianity has become increasingly associated with affirming clientelism and the accumulation of wealth in a way which is avowedly non-political but in practice legitimates the current political order. Meanwhile, although individual Muslims are more likely to enjoy high political office than was previously the case, Muslims are also more likely to locate their experience as symptomatic of a wider pattern of exclusion in Kenya and link this sense of local injustice to global inequalities.